Possible linkage between solar and geomagnetic activity and upper atmospheric phenomena - RAO, K. S. RAJA; DUBEY, R. A.; PATIL, S. R. (MAUSAM, 1978)
Solar flare effect on the upper atmosphere has been studied by examination of the geopotential height changes of 500, 300, 200 and 100 mb levels over Delhi and Trivandrum, following 9 solar flares of importance >= 2 in the winters of 1971 and 1972. There is a change in the geopotential height in low latitudes following a solar flare. Temperature height profiles derived from the meteorological rocket observations over Thumba reveals that a major flare of 2 August 1972 caused a temperature change of nearly 18°C in the height range of 66 to 78 km. Geopotential height changes in the different constant pressure levels over Delhi and Trivandrum following enhanced geomagnetic activity , suggest that this effect is manifest even in low latitudes. Cross spectrum analysis of the 10.7 cm solar flux and 100 and 50 mb temperatures over Delhi and Trivandrum do not indicate any relationship between the cyclicities in the solar flux and atmospheric parameters.